Forgotten Voices: Aromanians in Macedonia (1900-1941) - Minov, Nikola (Institute for Recent History of Serbia, 2024)
This study examines the demographic and cultural transformations of the Aromanian population in Macedonia from the early 20th century through the interwar period. It explores how the Aromanians navigated their complex identity amidst the pressures of Greek and Romanian influence while adapting to the changing political landscape. The research also assesses the impact of the Balkan Wars and World War I on their community.
Keywords: Aromanians, demographics, identity, migration, wars, deportation